Kecernaan Nutrien pada Babi Lokal Periode Pertumbuhan yang Diberi Ransum Mengandung Biji Asam Biokonversi Spontan (NUTRIENTS DIGESTIBILITY IN GROWING LOCAL PIG FED WITH DIET COMPOSED OF SPONTENOUS BIOCONVERTED-TAMARIND SEED) - Wea, Redempta; Wirawan, I Gusti Komang Oka; Koten, Bernadete Barek (Jurnal Veteriner; Vol 18 No 4 (2017)DO - 10.19087/jveteriner.2017.18.4.610, 2018)
A research aimed to evaluate nutrients digestibility in growing local male pig fed spontaneous bioconverted-tamarind seed has been done in animal feed technology laboratory of Kupang State Agricultural Polytechnic.The research used 25 local male grower pigs with body weight around 3-6 kg. The study used a randomized block design with five treatments, i.e. R0 = ration using tamarind seeds without bioconversion, R1 = ration using spontaneous bioconversion tamarinds for 24 hours, R2 = rations using spontaneous bioconversion tamarinds for 48 hours, R3 = rations using bioconversion tamarinds spontaneous for 72 hours, and R4 = rations using spontaneous bioconversion tamarinds for 96 hours. Each treatment was repeated five times in which each of them used five pigs. Parameters observed were nutrient digestibility (dry matter, crude protein, crude fat, crude fiber, and ash). The data were analyzed by using variance and continued by Duncan’s multiple range test to determine the differences between treatments. The results showed that the time of spontaneous bioconversion of tamarind seeds increased the digestibility of tamarind seed nutrients and it was concluded that the best time of spontaneous bioconversion was for 72 hours.